Passive functional mapping of receptive language cortex during general anesthesia using electrocorticography. (March 2023) - Nourmohammadi, Amin; Swift, James R.; de Pesters, Adriana; Guay, Christian S.; Adamo, Matthew A.; Dalfino, John C.; Ritaccio, Anthony L.; Schalk, Gerwin; Brunner, Peter
Graphical abstract: Highlights: Intraoperative electrocortical stimulation-based language mapping requires patients' awake cooperation and is not feasible in certain neurosurgical cases. Task-related broadband gamma (BBG) responses can be used to identify the language network during general anesthesia. Localizing receptive language cortex during general anesthesia expands the list of potential candidates for language mapping. Abstract: Objective: To investigate the feasibility of passive functional mapping in the receptive language cortex during general anesthesia using electrocorticographic (ECoG) signals. Methods: We used subdurally placed ECoG grids to record cortical responses to speech stimuli during awake and anesthesia conditions. We identified the cortical areas with significant responses to the stimuli using the spectro-temporal consistency of the brain signal in the broadband gamma (BBG) frequency band (70–170 Hz). Results: We found that ECoG BBG responses during general anesthesia effectively identify cortical regions associated with receptive language function. Our analyses demonstrated that the ability to identify receptive language cortex varies across different states and depths of anesthesia. We confirmed these results by comparing them to receptive language areas identified during the awake condition. Quantification of these results demonstrated an average sensitivity and specificity of passive language mapping during general anesthesia to be 49 ± 7.7% and 100%, respectively. Conclusion: Our results demonstrate that mapping receptive language cortex in patients during general anesthesia is feasible. Significance: Our proposed protocol could greatly expand the population of patients that can benefit from passive language mapping techniques, and could eliminate the risks associated with electrocortical stimulation during an awake craniotomy.